Replacement of two mandibular central incisors using a zirconium resin-bonded fixed partial denture: A clinical report - TÜRKER, ŞEBNEM BEGÜM (MOSBY, INC, 2005)
Maxillary and mandibular anterior tooth loss may cause esthetic and functional problems. Successful treatment for these situations may necessitate a minimally invasive technique to preserve sound remaining abutment tooth structure. This article describes the use of zirconium resin-bonded fixed partial denture as a conservative treatment option for the replacement of 2 mandibular central incisors.
Keywords: FOLLOW-UP; PROSTHODONTICS; RESISTANCE; PROSTHESES; RETENTION